Hubungan Pengetahuan Dengan Perilaku Dan Rasionalitas Penggunaan Parasetamol Sebagai Upaya Swamedikasi Di Kalangan Ibu Rumah Tangga - Najmi Hilaliyati; Izza Aulia Rizqika Nasution; Reza Laila Najmi; Efilia Meirita; Fitratul wahyuni; Fitria Anggraini (LPPM, Universitas Muhammadiyah Riau, 2025)
The use of over-the-counter drugs such as paracetamol in self-medication is commonly practiced by the public, particularly among housewives. This study aims to determine the correlation between the level of knowledge and the behavior and rationality of paracetamol use in self-medication among housewives in Nagari Sungai Pua. The research employed an observational design with a cross-sectional approach. Samples were selected using purposive sampling, and data were collected through a structured questionnaire. The results showed that the majority of housewives had a good level of knowledge (77.3%), demonstrated positive behavior (63.9%), and used paracetamol rationally (86.6%). Spearman correlation analysis indicated a significant relationship between knowledge and behavior (p < 0.05), as well as between knowledge and the rationality of paracetamol use (p < 0.05). The study concludes that there is a significant correlation between the level of knowledge of housewives and their behavior and rational use of paracetamol in self-medication. It is recommended to enhance public education regarding rational drug use through health professional counseling.